2006
DOI: 10.1111/j.1460-9568.2006.04932.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of TRPC1 receptors in dendrites of rat substantia nigra: a confocal and electron microscopy study

Abstract: Transient receptor potential channels (TRPC) are plasma membrane, non-selective cationic channels and have been proposed as candidates involved in the regulation of cellular Ca2+ influx. The expression, at mRNA level, of several TRPCs has been demonstrated recently in dopaminergic neurons of the substantia nigra (SN). The aim of the present study was to characterize the expression of TRPC1, at a protein level, in the substantia nigra neurons and non-excitable cells of Wistar rats. Single-label immunohistochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 27 publications
(49 reference statements)
3
20
0
1
Order By: Relevance
“…In the mouse hippocampus, cells expressing TRPC4 protein can be found together with neurons expressing TRPC1 and TRPC5 (von Bohlen und Halbach et al 2005;Chung et al 2006). TRPC1 and TRPC5 protein have also been found to be expressed in neurons in other areas of the rat brain, such as the substantia nigra (De March et al 2006;Martorana et al 2006). TRPC3 protein has further been observed to be expressed in the substantia nigra, although TRPC3 protein in this brain area is mainly expressed by oligodendrocytes (Fusco et al 2004).…”
Section: Resultsmentioning
confidence: 92%
“…In the mouse hippocampus, cells expressing TRPC4 protein can be found together with neurons expressing TRPC1 and TRPC5 (von Bohlen und Halbach et al 2005;Chung et al 2006). TRPC1 and TRPC5 protein have also been found to be expressed in neurons in other areas of the rat brain, such as the substantia nigra (De March et al 2006;Martorana et al 2006). TRPC3 protein has further been observed to be expressed in the substantia nigra, although TRPC3 protein in this brain area is mainly expressed by oligodendrocytes (Fusco et al 2004).…”
Section: Resultsmentioning
confidence: 92%
“…Although a few reported studies have examined TRPC channels in select brain regions, an extensive and comprehensive description of the brain-wide expression of TRPC4 and 5 channels is lacking [17],[18],[19],[20],[21],[22],[23]. In this study we sought to identify the expression pattern and suggest a possible function of the TRPC4 and 5 channels in the rodent brain.…”
Section: Introductionmentioning
confidence: 99%
“…Some TRPC proteins are expressed in the CNS and function as important regulators during development (Jia et al, 2007;Li et al, 1999). TRPC1 is mainly localized to dendritic processes of dopaminergic neurons (Martorana et al, 2006), whereas TRPC6 is localized to proximal dendrites and the axon hillock (Giampa et al, 2007). Interestingly, TRPC5 is preferentially localized to the neuronal nuclei in the substantia nigra (De March et al, 2006), and TRPC3 is mainly found in oligodendrocytes (Fusco et al, 2004).…”
Section: Introductionmentioning
confidence: 99%